2011
DOI: 10.1074/jbc.m111.262337
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Aggregation and Assembly

Abstract: The mechanism of fibronectin (FN) assembly and the selfassociation sites are still unclear and contradictory, although the N-terminal 70-kDa region ( I 1-9) is commonly accepted as one of the assembly sites. We previously found that I 1-9 binds to superfibronectin, which is an artificial FN aggregate induced by anastellin. In the present study, we found that I 1-9 bound to the aggregate formed by anastellin and a small FN Fibronectin (FN)2 is a secreted protein expressed in the liver and circulated in blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 57 publications
3
28
0
Order By: Relevance
“…We also found previously that introducing a disulfide bond in III 2, which stabilized folding, significantly reduced the level of the FN matrix. 16 The binding of the N-terminal region, I 1–5, to III 2 also agrees with the N-terminal 30–40 nm overlap between FN molecules in matrix fibrils observed by super-resolution microscopy. 33 …”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…We also found previously that introducing a disulfide bond in III 2, which stabilized folding, significantly reduced the level of the FN matrix. 16 The binding of the N-terminal region, I 1–5, to III 2 also agrees with the N-terminal 30–40 nm overlap between FN molecules in matrix fibrils observed by super-resolution microscopy. 33 …”
Section: Discussionsupporting
confidence: 75%
“…We previously reported that the folding and stability of FNIII domains were crucial for anastellin-induced FN aggregation. 15,16 We suggest that the GFND mutations destabilize the FNIII domains and these unstable FNIII domains may slowly form nonfibrillar aggregates in the kidney. In the case of the Y973C mutant, it is also possible that unusual disulfide bond formation, even in the case of a heterozygous mutation, enhances nonfibrillar aggregation.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations